1988
DOI: 10.1172/jci113605
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid synthesis in man. In vivo activity of the 25-hydroxylation pathway.

Abstract: During biosynthesis of bile acid, carbons 25-26-27 are removed from the cholesterol side-chain. Side-chain oxidation begins either with hydroxylation at the 26-position, in which case the three-carbon fragment is released as propionic acid, or with hydroxylation at the 25-position, in which case the threecarbon fragment is released as acetone. We have previously shown in the rat that the contribution of the 25-hydroxylation pathway can be quantitated in vivo by measuring production of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…This finding is in accordance with the concept that the 25-hydroxylase pathway is particularly important for cholic acid biosynthesis [45,46]. Honda et al [47] reported that murine It has been estimated that about 5% of total bile acids are formed by the 25-hydroxylase pathway in healthy humans [53]. However, when the 27-hydroxylase pathway for side chain oxidation is blocked, e.g.…”
Section: -Hydroxylase Pathwaysupporting
confidence: 86%
“…This finding is in accordance with the concept that the 25-hydroxylase pathway is particularly important for cholic acid biosynthesis [45,46]. Honda et al [47] reported that murine It has been estimated that about 5% of total bile acids are formed by the 25-hydroxylase pathway in healthy humans [53]. However, when the 27-hydroxylase pathway for side chain oxidation is blocked, e.g.…”
Section: -Hydroxylase Pathwaysupporting
confidence: 86%
“…Cholic acid is formed in these patients by a pathway involving 25-hydroxylated bile alcohols as intermediates. Under normal conditions this alternative pathway is of little or no importance, both in rats and man (21,22). Due to the reduced formation of bile acids, the negative feedback of the cholesterol 7␣-hydroxylase is reduced, resulting in an up-regulation of this enzyme.…”
mentioning
confidence: 99%
“…A "25-hydroxylation pathway", initiating 25-hydroxylation of THC, is also believed to be involved in cholic acid biosynthesis in patients with CTX due to completely defective mitochondrial 26hydroxylase (2). The 25-hydroxylation pathway is thought to be an alternative pathway for cholic acid formation even in healthy individuals, since 5b-cholestane-3a,7a,12a,24,25-pentol is a normal constituent of urine from normal subjects and rats (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%